All You Need Is Facebook Friends? Associations between Online and Face-to-Face Friendships and Health - Lima, Maria Luisa; Marques, Sibila; Muiños, Gabriel; Camilo, Cristina (Frontiers in Psychology, 2017)
Positive social relations are known to have a beneficial impact on health, however little is known about the links of health with online relationships. In this study we compare face-to-face and virtual friendships in their association with health. By building on previous results of studies conducted on the well-being of college students, we expect to find stronger associations of face-to-face friendships with health than of those established through Facebook. Furthermore, we expect to test the mediating role of social capital variables in this process. Two large-scale studies conducted in community samples (Study 1 = 350 urban residents; Study 2 = 803 urban and rural residents) show that the number and quality of face-to-face friendships are directly associated with self-reported health status, however the same does not occur with Facebook friendships. Moreover, the association of face-to-face friendships with health is totally mediated by bonding (mostly) but also bridging social capital. These results, replicated in both studies, were found by controlling for confounding variables such as age, gender, education, living alone, self-esteem and socioeconomic status. This pattern of results emphasizes the gains of face-to-face over online friendships for individuals’ health status in community samples.